PP054 The All Wales Patient Reported Outcome Measures (PROMs), Patient Reported Experience Measures (PREMs) and Effectiveness Program. (2017) - Withers, Kathleen; Palmer, Robert; Carolan-Rees, Grace
Abstract : INTRODUCTION: Prudent health care aims to do the minimum needed to achieve the greatest patient benefit. This aim relies on the availability of evidence on the safety and efficacy of interventions to support decision making. The principles of prudent healthcare support co-production, whereby service users contribute to service provision. Collection of patient reported data is becoming more widespread, however use of this data to inform decision making is limited. METHODS: A national patient reported outcome measures (PROMs) program has been formed supported by the Welsh Government, Welsh Health Boards and the NHS Wales Informatics Service. An electronic platform has been developed to facilitate collection of PROMs and patient reported experience measures (PREMs) from patients treated in secondary care. We collected baseline PROMs where possible and invited patients to submit PROMs and PREMs post-treatment. Data collected included EuroQuol five dimensions questionnaire (EQ5D), co-morbidities, body mass index (BMI), smoking history and alcohol intake. Disease specific tools were used where available and responses linked to clinical data. Individual level data will be available during clinic consultations, and collated data analyzed on national and health board levels to assess clinical effectiveness. The platform is currently being piloted in several sites across Wales. RESULTS: Initial baseline pilot data from hip replacement patients found that over 55 percent of responders were classed as overweight or obese, with over 80 percent carrying out less than the national guidelines for exercise. The baseline scores for hip patients were; EQ-5D Index (Mean .29, median .29, range (-.59 -1)), EuroQol-visual analogue scales (EQ-VAS) (Mean 57.8, median 60, range (0:100)), and Oxford Hip Score (Mean 14.9, median 14, range (0:48)). When compared to baseline scores collected by NHS England in 2015/16 (1), the average EQ5D Index and Oxford Hip Score collected in Wales was lower than that in England (p< .05). CONCLUSIONS: The program will provide a large dataset from patients across all of Wales with data on numerous chronic and acute conditions. The data collected will facilitate service improvements and will inform decision making as part of the prudent healthcare agenda.